2020
DOI: 10.3390/rs12172682
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Influences of SWOT Sampling and Errors on Ocean Eddy Observation

Abstract: The mission of Surface Water and Ocean Topography (SWOT) is scheduled to be launchedin 2022, and global ocean eddies with radius scales of larger than 10 km are expected to be observedfrom space. However, there are still open questions about the capability of SWOT to detect oceaneddies. Based on ocean model data and SWOT orbit, this study simulates along-track observationof SWOT. Two eddy datasets are derived from simulated observation data via mapping and eddyidentification procedures, one of which includes S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…First, a global data set will be identified with improvements in computational efficiency. Second, in this study, we extracted typical events for validation due to the limited accuracy of our data set caused by the SLA data resolutions; the accuracy of our data set can be optimized with improvements in data resolution promoted by the progress of ocean remote sensing technology [38]. Third, our algorithm for tracking eddy splitting and merging events is based on the nature of eddies in two-dimensional SLA data.…”
Section: Discussionmentioning
confidence: 99%
“…First, a global data set will be identified with improvements in computational efficiency. Second, in this study, we extracted typical events for validation due to the limited accuracy of our data set caused by the SLA data resolutions; the accuracy of our data set can be optimized with improvements in data resolution promoted by the progress of ocean remote sensing technology [38]. Third, our algorithm for tracking eddy splitting and merging events is based on the nature of eddies in two-dimensional SLA data.…”
Section: Discussionmentioning
confidence: 99%
“…where p represents the pressure, ρ represents the density that can be decomposed as: 𝜌 = 𝜌 0 + 𝜌 ′ ( 6 ) where 𝜌 0 is the reference potential density (1027.5 kg/m3), 𝜌 ′ is the potential density anomaly. Equation ( 5) can also be expressed in the form: ( 7 ) In this equation, 𝑝 𝐴 refers to the atmospheric surface pressure, 𝑝 𝐵 refers to the bottom pressure of ocean, ζ is the SSH referenced to z = 0, and -h is the depth of the ocean. Transforming the above formula as…”
Section: Steric Heightmentioning
confidence: 99%
“…The Tiangong-2 [4] and soonto-be-launched "Surface Water Ocean Topography (SWOT) Mission" [5], "Guanlan" [6] and other possible missions will provide high-precision two-dimensional (2D) SSH data as the basis of the study of short-wavelength scale dynamic processes. Nevertheless, the simulation showed that more than one-third of eddies cannot be observed by SWOT in the high eddy kinetic energy (EKE) region (the Kuroshio Extension), even without considering the effect of internal tides [7]. Meanwhile, with the development of altimeter technology, the validation methods for conventional altimeters no longer meet the needs of many future altimeter missions, especially the validation requirements for WIA 2D data areas [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The planned SWOT observatory [1][2][3][4], a collaboration between the US and French space agencies slated for launch in 2022, is designed to make high resolution, accurate two-dimensional measurements of ocean topography using SAR interferometry [5][6][7][8]. This unprecedented set of measurements would allow characterization of ocean mesoscale and sub-mesoscale dynamic processes [9][10][11] that are crucial to understanding and quantifying the exchange of energy between ocean layers and their impact on local and global carbon and energy budgets as well as nutrient transport [12,13]. The primary instrument on board the SWOT observatory enabling this unique set of measurements is KaRIn [14,15], a Ka-band (35 GHz) near-nadir radar interferometer capable of measuring sea-surface height with centimetric accuracy at kilometer scale resolutions [16], complemented with a nadir altimeter [17], GPS and DORIS [18] receivers and a three-frequency radiometer [19].…”
Section: Introductionmentioning
confidence: 99%